2009
DOI: 10.1589/jpts.21.169
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Influence of the Pulmonary Function on the Angles of Thoracic Kyphosis and Lumbar Lordosis in Community-Dwelling Elderly Women

Abstract: Abstract.[Purpose] The purpose of this research was to investigate the impact of vertebral column alignment on respiratory function in elderly female subjects.[Subjects] The subjects were 23 female community-dwelling elderly (age: 76.8 ± 5.1 years old, BMI: 23.6 ± 2.3).[Methods] The thoracic kyphosis angle was determined by adding the angles of the superior and inferior vertebral bodies from the 1st to the 12th thoracic vertebrae, and the lumbar lordosis angle was determined by adding the angles of the superio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 14 publications
(17 reference statements)
0
16
1
Order By: Relevance
“…However, VC and FEV1 were not significantly different between and within groups before and after the intervention. Horie et al 5 ) measured respiratory function using FVC and % FVC and reported that the lumbar lordosis angle was more related to vertebral column alignment than thoracic kyphosis. In the present study, although the thorax improvement exercise program was not sufficient for improving flow volume, it was deemed effective in improving mobility of the rib cage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, VC and FEV1 were not significantly different between and within groups before and after the intervention. Horie et al 5 ) measured respiratory function using FVC and % FVC and reported that the lumbar lordosis angle was more related to vertebral column alignment than thoracic kyphosis. In the present study, although the thorax improvement exercise program was not sufficient for improving flow volume, it was deemed effective in improving mobility of the rib cage.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly women with ARH often report difficulties with physical performance because of changes in vertebral column alignment, which affects the quality of life of patients in relation to their health 4 ) . In addition, ARH limits the movement of the rib cage, which is connected to the thoracic spine, resulting in difficulties with pulmonary function 5 ) . Horie et al 5 ) reported that the thoracic vertebrae forms costotransverse joints with the head of the rib.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lumbar curvature was found to be significantly correlated between diaphragm muscle thickness during deep inspiration and respiratory muscle strength. Diaphragm muscle is the main muscle of inspiration34,35 and the main attachment of the diaphragm muscle is at the lumbar spine 12. Thus, a correlation between diaphragm muscle thickness and lumbar curvatures may be possible.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between respiratory function and thoracolumbar curvatures has been discussed in the literature 12–15. A significant correlation between only lumbar curvature angle with forced vital capacity (FVC; r =−0.65), %FVC ( r =−0.63) and forced expiratory volume (FEV; r =−0.50) was reported among community-dwelling older females 12.…”
Section: Introductionmentioning
confidence: 99%